Praziquantel activates a native cation current in Schistosoma mansoni - Chulkov, Evgeny G.; Rohr, Claudia M.; Marchant, Jonathan S. (Frontiers in Parasitology, 2023)
Praziquantel (PZQ), an anthelmintic drug discovered in the 1970s, is still used to treat schistosomiasis and various other infections caused by parasitic flatworms. PZQ causes a triad of phenotypic effects on schistosome worms – rapid depolarization, muscle contraction, and damage throughout the worm tegument. The molecular target mediating these effects has been intimated as a Ca2+-permeable ion channel, but native currents evoked by PZQ have not been reported in any schistosome cell type. The properties of the endogenous PZQ activated conductance therefore remain unknown. Here, invasive electrophysiology was used to probe for responses to PZQ from different locales in a living schistosome worm. No direct response was seen in tegument-derived vesicles, or from the sub-tegumental muscle layer despite the presence of voltage-operated currents. However, PZQ rapidly triggered a sustained, non-selective cation current in recordings from neuronal tissue, targeting both the anterior ganglion and the main longitudinal nerve cord. The biophysical signature of this PZQ-evoked current resolved at single channel resolution matched that of a transient receptor potential ion channel named TRPMPZQ, recently proposed as the molecular target of PZQ. The endogenous PZQ-evoked current was also inhibited by a validated TRPMPZQ antagonist. PZQ therefore is a neuroactive anthelmintic, causing a sustained depolarization through ion channels with the characteristics of TRPMPZQ.